in general this is complicated but we only care about it for � μ G μ a 0 then

In general this is complicated but we only care about

This preview shows page 21 - 25 out of 38 pages.

in general, this is complicated — but we only care about it for η μ G μ a = 0 — then the first term on the RHS vanishes and the change in η μ G μ a is independent of G — just a constant — infinite but uninteresting — NO GHOSTS this is called “temporal gauge” if η μ η μ > 0 , it is called “axial gauge” if η μ η μ < 0 , and it is called “light-cone gauge” if η μ η μ = 0 — so you see that there are many gauges in which gauge fixing works very simply — you just impose a condition on G μ to break the symmetry and calculate — for gauge invariant quantities, the results are independent of which gauge you chose 21
Image of page 21
Δ( G ) = Π x,a fl fl fl fl [ μ G μ Ω a ] [ d Ω] fl fl fl fl η μ G μ Ω a =0 because we are evaluating at η μ G μ a = 0 we only need infinitesimal transformations Ω = 1 + idω a T a G μ = T a G μ a Ω G μ Ω - 1 - i Ω μ Ω - 1 dG μ a = i [ a T a , T b G μ b ] - T a μ a = - T a μ a - i [ T b G μ b , dω a T a ] = - D μ ( T a a ) d ( η μ G μ a ) = η μ dG μ a = i [ a T a , T b η μ G μ b ] - T a η μ μ a in general, this is complicated — but we only care about it for η μ G μ a = 0 — then the first term on the RHS vanishes and the change in η μ G μ a is independent of G — just a constant — infinite but uninteresting — NO GHOSTS this is called “temporal gauge” if η μ η μ > 0 , it is called “axial gauge” if η μ η μ < 0 , and it is called “light-cone gauge” if η μ η μ = 0 — so you see that there are many gauges in which gauge fixing works very simply — you just impose a condition on G μ to break the symmetry and calculate — for gauge invariant quantities, the results are independent of which gauge you chose 22
Image of page 22
funny propagator — look at one G μ a and drop the a — assume η μ η μ 6 = 0 L = - 1 4 μ G ν - ν G μ ·‡ μ G ν - ν G μ · + μ G μ + s μ G μ + · · · K equation of motion η μ G μ = 0 G ν equation of motion μ L μ G ν = L ∂G ν - μ μ G ν - ν G μ · = ν + s ν 0 = ν ν + s ν · K = - ( ∂s ) ( η∂ ) ( η∂ )( ∂G ) = - η ν μ μ G ν - ν G μ · = η ν ν + s ν · = - ( ηη ) ( ∂s ) ( η∂ ) + ( ηs ) ( ∂G ) = ( η∂ )( ηs ) - ( ηη )( ∂s ) ( η∂ ) 2 - ( ∂∂ ) G ν = s ν - η ν ( ∂s ) ( η∂ ) - ν ( η∂ )( ηs ) - ( ηη )( ∂s ) ( η∂ ) 2 = - - g νμ + ν η μ + η ν μ ( η∂ ) - ( ηη ) ν μ ( η∂ ) 2 s μ 23
Image of page 23
another example of gauge fixing functions — f ( G, φ ) = Π x,a δ μ G μ a ( x ) · I call this “Landau gauge” (also called “Lorenz gauge” or “Lorentz gauge”) K a μ G μ a so that the equation of motion for K a is μ G μ a = 0 what is Z f ( G Ω , φ Ω ) [ d Ω] ? Δ( G, φ ) - 1 = Z f ( G Ω , φ Ω ) [ d Ω] = Z Π x,a δ μ G μ Ω a ( x ) · [ d Ω] = Z Π x,a δ μ G μ Ω a ( x ) · 1 `fl fl fl fl [ d∂ μ G μ Ω a ] [ d Ω] fl fl fl fl [ d∂ μ G μ Ω a ] = Π x,a ˆ 1 , fl fl fl fl [ d∂ μ G μ Ω a ] [ d Ω] fl fl fl fl μ G μ Ω a =0 !
Image of page 24
Image of page 25

You've reached the end of your free preview.

Want to read all 38 pages?

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture